Mothers of children with disabilities: exploring lived experiences, challenges, and divorce risk - Alsamiri, Yasir A.; Alaghdaf, Ayesha A.; Alsawalem, Ibraheem M.; Allouash, Basheer A.; Alfaidi, Seham D. (Frontiers in Psychology, 2024)
This qualitative study explores the psychological challenges faced by divorced Saudi mothers who are raising children with disabilities. The study highlights the impact of having a child with a disability on marital stability and family issues, and the psychological challenges experienced by single mothers. Using semi-structured in-depth interviews, data were collected from five divorced mothers recruited from a private daycare center. Participants ranged in age from 34 to 53, each with one child with a disability, and an average divorce period of four years. The thematic analysis revealed that single/divorced Saudi mothers of children with disabilities experienced significant psychological strain characterized by fear, shock and attempts at religious acceptance to cope with their child’s condition. Additionally, these mothers reported facing substantial social challenges, including societal ridicule and limited remarriage prospects, highlighting the broader impact of having a child with a disability on their lives. The study underscores the need for tailored psychological support and interventions for families of children with disabilities, especially for mothers who are significantly impacted by the challenges associated with their child’s condition. Additionally, the study emphasizes the negative impact of societal attitudes towards disability, which can contribute to social problems and psychological distress for families. The study’s findings suggest the need for specialized clinics and support groups to help families cope with the unique challenges they face.